2007
DOI: 10.1097/mca.0b013e328056dd46
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of amount of contrast utilized in patients undergoing percutaneous coronary procedures

Abstract: Data from our study could guide the coronary angiographer in moderating the volume of contrast utilized as well as assist with the elective planning of complex therapeutic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Marenzi et al 1 has shown increased CV in those with disease in the left coronary arteries compared to those with disease in the right coronary arteries; however, similar to the study by Mager et al, their sample size was also limited to patients with STEMI. In contrast, the study by Pradhan et al 12 did not find any difference in CV in patients with diseased left versus right coronary arteries. None of the above-mentioned studies have demonstrated the association of CV use with the number of obstructed vessels.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Marenzi et al 1 has shown increased CV in those with disease in the left coronary arteries compared to those with disease in the right coronary arteries; however, similar to the study by Mager et al, their sample size was also limited to patients with STEMI. In contrast, the study by Pradhan et al 12 did not find any difference in CV in patients with diseased left versus right coronary arteries. None of the above-mentioned studies have demonstrated the association of CV use with the number of obstructed vessels.…”
Section: Discussionmentioning
confidence: 71%
“…Increased use of CV has been associated with lesions in the left coronary arteries compared to the right coronary arteries, 1 but the data are conflicting. 12 The association of CV and severity and complexity of coronary artery disease (CAD) remains unknown. Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) is an angiographic tool for grading CAD complexity and severity.…”
Section: Introductionmentioning
confidence: 99%